Qualidade de sementes de Lolium multiflorum Lam. e avaliação pelo teste de tetrazólio - Huth, Caroline (2019)
Among the forages used in southern Brazil, annual ryegrass is one of the most important winter pastures, which meets the food demand of cattle and sheep. However, there is a low rate of utilization of ryegrass seeds, favoring the oscillation of seed quality of this species, as well as illegal trade in seeds. Among the tests to evaluate the quality of ryegrass seeds is the tetrazolium test, which generates results faster than the germination test, facilitating the purchase and handling of the seeds. The objective of this research was the physical and physiological quality of the samples of ryegrass seeds analyzed in laboratories accredited at the Ministry of Agriculture, Livestock and Supply (MAPA) of Rio Grande do Sul; to improve the methodology of the tetrazolium test in Lolium multiflorum seeds, with more precise definitions for reliability of the results and to facilitate their interpretation. The data of 3975 ryegrass samples analyzed from the period 2014 to 2017 were compiled. From the data of germination, purity and other seeds by number, a descriptive analysis of the data in the time (years), yield crop, cultivar , category and region of origin. Also, the percentage of samples within the standards recommended for commercialization, for the variables: germination, pure seeds, seeds of cultivated species, wild, noxious tolerated and noxious prohibited. For the tetrazolium test methodology, four replicates of 50 seeds of four lots of ryegrass seeds of high and low physiological quality were used in completely randomized design, 2 x 3 bi-factorial, two pre-wetting conditions of the seeds before staining (in germitest paper moistened for a period of 16 hours and direct soaking in water for 3 hours at 68°F) and three soaking times (4, 5 and 6 hours in 0.5% of 2,3,5-triphenyl tetrazolium at 86°F). For the physical quality of annual ryegrass lots, there is greater variability in the number of seeds in cultivated, wild and noxious species tolerated. From 2013 to 2016, there was an improvement in the quality of a lot of ryegrass, initiated by the laboratories of Rio Grande do Sul, that is, a 2013 crop and 2014 harvests under 18 years of commercialization, 57.96%, and 2014, 2015 and 2016 crops with the highest percentage, 89.60%, 91.39% and 91.34%, respectively. The quality of samples in procedure of the lots of seeds of ryegrass, in regions of predominance of the cattle to percentage of lots now to merchandise was minor. The result of the viability of the tetrazolium test for ryegrass seeds is not necessarily the result of normal seedlings by the germination test, as the yield patterns can not be the same for the two testicles. The use of classes 1 to 3, of the proposed scale of tetrazolium test, is an indicator of efficacy of ryegrass seed batch, using a preconditioning methodology on paper with 4 hours of staining.